Review of agro waste plastic composites production. - Zahari, Nur Ismarrubie; Salit, Mohd Sapuan; Alhaji Abba, Hammajam (2013)
This article reviews the literature reports base on agro waste plastic composites using different fiber as fillers and reinforcements. Various processing methods and conditions; compression molding process, injection molding, and extrusion method are used in the composites productions. Characterization challenges associated with the agro waste plastic composites productions were also examined. Thus, the findings of this research review can be use as a data base for further inquiring into the agro waste plastic composites in a view to enhance the development of the sector.